Genome-wide Characterization of the JmjC Domain-Containing Histone Demethylase Gene Family Reveals GhJMJ24 and GhJMJ49 Involving in Somatic Embryogenesis Process in Cotton - Li, Yan; Zhu, Shouhong; Yao, Jinbo; Fang, Shengtao; Li, Tengyu; Li, Bei; Wang, Xinyu; Wang, Mingyang; Wu, Lanxin; Pan, Jingwen; Feng, Xuemei; Chen, Wei; et al. (Frontiers in Molecular Biosciences, 2022)
The JmjC domain-containing (JmjC) protein family, an important family of histone demethylase in plants, can directly reverse histone methylation and play important roles in various growth and development processes. In the present study, 51 GhJMJ genes were identified by genome-wide analysis in upland cotton (Gossypium hirsutum), which can be categorized into six distinct groups by phylogenetic analysis. Extensive syntenic relationship events were found between G. hirsutum and Theobroma cacao. Further, we predicted the putative molecular regulatory mechanisms of the JmjC gene family in cotton. GhJMJ24 and GhJMJ49 were predominantly expressed in embryogenic callus compared to nonembryogenic callus in tissue culture, which might be regulated by transcription factors and microRNAs to some extent. Further experiments indicated that GhJMJs might interact with SUVH4, SUVH6, DDM1, CMT3 and CMT1 in the nucleus, potentially in association with demethylation of H3K9me2. Taken together, our results provide a basis for future research on the biological functions of GhJMJ genes in cotton, especially in somatic embryogenesis in cotton tissue culture.